2012
DOI: 10.3109/09537104.2012.712168
|View full text |Cite
|
Sign up to set email alerts
|

Platelets and acute cerebral infarction

Abstract: Stroke is worldwide a leading cause of death and disability. Its etiology is regarded as heterogeneous. Platelets are implicated in its pathophysiology, but our understanding of their specific role is incomplete. Only sparse and conflicting information exists about platelet reactivity and activity in acute stroke. Some scientists take the view that platelets activate in conjunction with acute cerebral infarctions. Others put forward evidence corroborating the contrary notion. Increased soluble P-selectin as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Three studies showed that patients with AS had higher PC than controls [24,35,36]. Eleven studies demonstrated lower PC in the patient group [12][13][14]23,[25][26][27]30,32,35,43], and 11 studies found no difference in PC between patients and controls (Table I, Supplementary Table VI) [11,15,28,29,33,37,41,42,44,46,47]. One study did not provide PC results.…”
Section: Pcmentioning
confidence: 99%
“…Three studies showed that patients with AS had higher PC than controls [24,35,36]. Eleven studies demonstrated lower PC in the patient group [12][13][14]23,[25][26][27]30,32,35,43], and 11 studies found no difference in PC between patients and controls (Table I, Supplementary Table VI) [11,15,28,29,33,37,41,42,44,46,47]. One study did not provide PC results.…”
Section: Pcmentioning
confidence: 99%
“…Our understanding of the roles of selectins in various neurological disorders lies in its infancy. In stroke, E-and P-selectin have been shown to affect platelet and endothelial activities (Beer et al, 2011;Jaremo et al, 2012), which in turn modulate inflammatory responses and degeneration (Ma et al, 2012). Interestingly, polymorphisms in L-selectin appear to increase the risk of stroke (Wei et al, 2011).…”
Section: Selectins-selectinsmentioning
confidence: 99%
“…Citrate anticoagulated whole blood was used for analysing reactivity and activity of all platelets and, to minimise deviations, due to sample aging the determinations were commenced approximately 2 hours after sampling. The number (%) of cells expressing P-selectin/ fibrinogen was visualised using a Beckman Coulter EPICS XL-MCL flow cytometer (Beckman Coulter, Inc., Brea, Cal, USA) [23], [24]. Platelets were identified with an antibody towards glycoprotein Ib.…”
Section: Methodsmentioning
confidence: 99%